THE INFLUENCE OF SERVICE KNOWLEDGE ON THE DECISION TO CHOOSE ISLAMIC FINANCIAL INSTITUTIONS - Wita Dwika Listihana; Idel Waldelmi; Afvan Aquino (Inovbiz: Jurnal Inovasi Bisnis, 2023)
Knowledge of services for Islamic financial institutions in the city of Pekanbaru, Riau, found the results that the level of public knowledge of services and decisions to choose Islamic financial institutions in the city of Pekanbaru in the good to very good category, this is also supported by the results of the SPSS 23 test that the level of service knowledge on the decision to choose Islamic financial institutions has a positive effect and has increased. This research was conducted in the city of Pekanbaru. The research method used is quantitative research and uses the SPSS 23 test tool. The sample size in the study was 110 customers, where the sample was taken 10 times the number of statement items on the questionnaire submitted to customers with a ratio of 1: 10 (11 x10) (Hair, et al 2014) multivariate data analysis.